2003
DOI: 10.3989/scimar.2003.67n4379
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of the Ebro River plume. Validation with field observations

Abstract: SUMMARY: The spreading of the plume induced by the freshwater discharge from the Ebro River into northwestern Mediterranean coastal waters was modelled using two numerical codes. The coastal current field was obtained with a finite difference hydrodynamic model based on a steady-state version of the shallow-water equations, whereas the freshwater dispersion was calculated with a Lagrangian code that solves the 3D convection-diffusion equation and reproduces turbulent diffusion using a "random-walk" algorithm. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 49 publications
(52 reference statements)
0
13
0
4
Order By: Relevance
“…Furthermore, the regional response to wind jets is not clear due to the complex bathymetry and the spatial variability of the wind jet. Durand et al (2002) and Mestres et al (2003) showed that the effects of the salinity river plume are important only near the river mouth (of the order of 10 km offshore from the river mouth).…”
Section: Study Area and Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the regional response to wind jets is not clear due to the complex bathymetry and the spatial variability of the wind jet. Durand et al (2002) and Mestres et al (2003) showed that the effects of the salinity river plume are important only near the river mouth (of the order of 10 km offshore from the river mouth).…”
Section: Study Area and Observationsmentioning
confidence: 99%
“…Under severe storm conditions (hurricanes and cyclones), this parameter influences the spatial and temporal evolution of the meteo-oceanographic variables. Other recent examples that use a fully numerical model to investigate the air-sea interaction and its effect on oceanographic processes are found in Nelson and He (2012) and Drews (2013).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of a strong pycnocline during summer, between 10 150 and 20 m depth in the Ebro shelf [Jordà, 2005;Bastida et al, 2012], decouples the processes between surface and deep layers [Jordà et al, 2005;Grifoll et al, 152 2013]. Additionally, Durand et al [2002] and Mestres et al [2003] showed that the effects of the river plume are important only near the river mouth (order of 154 10 km offshore from the river mouth). From their observations and numerical results, the NES is relatively far from the influence of the river.…”
mentioning
confidence: 99%
“…Este modelo ha sido aplicado con éxito a varios escenarios (Mestres et al 2003(Mestres et al , 2010.…”
Section: Modelos Numéricosunclassified